Dictionary Of Pirates (Wordsworth Reference) - Rogozinski, Jan (Wordsworth Editions Ltd, 1997)
This book is a unique and authoritative work of reference on a fascinating and engrossing subject and is much needed and long awaited addition to the literature and history of the Sea.
Keywords: Study & Teaching; Pirates; Reference; Dictionaries; Language Arts & Disciplines